2020
DOI: 10.1186/s12868-020-00574-4
|View full text |Cite
|
Sign up to set email alerts
|

Repeated social defeat promotes persistent inflammatory changes in splenic myeloid cells; decreased expression of β-arrestin-2 (ARRB2) and increased expression of interleukin-6 (IL-6)

Abstract: Background: Previous studies suggest that persistent exposure to social stress in mammals may be associated with multiple physiological effects. Here, we examine the effects of social stress in rats, i.e. repeated social defeat, on behavior, hypothalamic-pituitary-adrenal (HPA)-axis and immune system. Methods: A resident-intruder paradigm, where an intruder rat was exposed to social stress by a dominant resident rat for 1 hour each day for 7 consecutive days was used. The day after the last stress exposure in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 60 publications
3
10
0
Order By: Relevance
“…However, long-term NE exposure causing receptor desensitization may diminish the suppressive effects (Hadcock and Malbon 1988). As previously shown, a reduced ADRB2 gene expression in stress-induced rats compared with control rats was demonstrated (Rajalingam et al 2020). Similarly, the NE and NE + DEX treated EL-1 cells-but not DEX treatment alone-showed reduced ADRB2 expression supporting the hypothesis that persistent NE exposure affects receptor responsivity.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…However, long-term NE exposure causing receptor desensitization may diminish the suppressive effects (Hadcock and Malbon 1988). As previously shown, a reduced ADRB2 gene expression in stress-induced rats compared with control rats was demonstrated (Rajalingam et al 2020). Similarly, the NE and NE + DEX treated EL-1 cells-but not DEX treatment alone-showed reduced ADRB2 expression supporting the hypothesis that persistent NE exposure affects receptor responsivity.…”
Section: Discussionsupporting
confidence: 73%
“…The present study showed a clear association between reduced social interaction and increased level of circulating NE in rats previously exposed to repeated social defeat. Taken together with our recent observation that repeated social defeat induced a persistent decrease in the myeloid ADRB2 gene expression of the same stress-exposed animals (Rajalingam et al 2020), this suggests that exposure to ongoing and repeated social defeat may affect future social behavior in animals. Hence, our present in vivo and in vitro data point to a link between social stress, fear, social withdrawal, and NE-ADRB2 signaling.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Previous findings suggest that environmental stressors, such as repeated social defeat (Jacobsen et al, 2020;Rajalingam et al, 2020), may be associated with fear and behavioral alterations (McKim et al, 2018;Wohleb et al, 2014). For example, repeated social defeat in social mammals triggers activation of subconscious parts of the brain, which in turn promotes nervousness (Rajalingam et al, 2021;Wohleb et al, 2014).…”
Section: Introductionmentioning
confidence: 99%